Self-assembled rows of Ni porphyrin dimers on the Ag(111) surface - SENGE, MATHIAS; SERGEEVA, NATALIA (My University, 2010)
The growth and ordering of 5-(10,15,20-triphenylporphyrinatonickel(II))dimer (NiTPP-dimer) molecules on the Ag(111) surface have been investigated using scanning tunnelling microscopy/spectroscopy (STM/STS) and low-energy electron diffraction (LEED). At one monolayer (ML) coverage the NiTPP-dimer forms a well-ordered close-packed molecular layer in which the porphyrin molecules have a flat orientation with the molecular plane lying parallel to the substrate. STM and LEED data obtained from one monolayer of the NiTPP-dimer on the Ag(111) surface show the formation of three domains which grow along the main crystallographic directions of the substrate. Scanning tunnelling spectroscopy data obtained from the NiTPP-dimer on the Ag(111) surface show good agreement with optical band gap measurements and density functional theory calculations.
PUBLISHED
Keywords: Physical chemistry; Scanning tunnelling spectroscopy; Nanoscience & Materials